Enhancing contrast agents and radiotracers performance through hyaluronic acid-coating in neuroradiology and nuclear medicine - Ganau, M; Syrmos, N; D'Arco, F; Ganau, L; Chibbaro, S; Prisco, L; Ligarotti, G; Ambu, R; Soddu, A (Hellenic Society of Nuclear Medicine, 2017)
The use of hyaluronic acid nanoshells has been proposed to encapsulate prodrugs and exploit the mechanisms of interactions between living cells, like endocytes or cancer cells and hyaluronic acid, which is a natural component of the extracellular matrix. In this review we describe the potential and the limits of this promising research trend and discuss the theoretical advantages of such an engineering approach. Is it a possible scalability to increase the efficacy and biodegradability of molecules like contrast media and radiotracers especially for neuroradiology and nuclear medicine studies.